Sociodemographic and clinical characteristics of adolescent candidates for blood donation in a hemotherapy service - Fernanda Duarte Siqueira; Nara Marilene Oliveira Girardon-Perlini; Anelise Levay Murari; Carla Tatiana dos Santos Coelho; Lauvir Freitas Carneiro (Universidade Federal de Santa Maria, 2020)
Objective: to know the sociodemographic and clinical characteristics of adolescents aged 16 and 17 who are candidates for blood donation in a Regional hemotherapy service in the State of Rio Grande do Sul. Method: cross-sectional, descriptive study, developed based on the records of a hemoterapy service database from January 2012 to December 2016, according to the criteria for expanding the selection of donors in Ordinance No. 1.353 / 2011. Results: the total number of blood donation candidates between 16 and 17 years old was 473 people, with a predominance of candidates suitable for donation (78.2%), female (57.5%), Caucasian (72.5% ), who donated for the first time (86%) voluntarily. Conclusion: the possibility of blood donation, including adolescents, needs to be widely publicized and marketing and health education actions used as strategies for raising awareness, attracting and retaining customers.